EFFECT OF BIOSTIMULATOR NORMS ON STEM GROWTH AND LEAF FORMATION IN SESAME CULTIVARS PLANTED IN THE SUMMER PERIOD - Yuldasheva Zulfiya Kamalovna; Usmanova Nilufar Avaz kizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: This article examines the effects of various biostimulants on stem growth and leaf formation in sesame varieties during the flowering and boll formation phases. The study found that treating the seeds of the Qora Shahzoda (Qora shahzoda) sesame variety with the Tandem 10% biostimulant at a rate of 0.4 l/t + 0.6+0.8 l/ha during the growing season promoted better stem growth and increased leaf formation. For the Sadaf variety, treating the seeds with the Immunoactive biostimulant at a rate of 30 ml/t + 35+40 ml/ha during the growing season yielded superior results compared to the use of Tandem 10% biostimulant and Fitovak 20% immunostimulator.